ADVICE PLANNING SYSTEM PADA DINAS PEKERJAAN UMUM DAN PENATAAN RUANG TATA KOTA PANGKALPINANG BERBASIS ANDROID - Sulaiman, Rahmat; Raya, Agustina Mardeka; Cahya Saputra, Kornelius Eko (ISTEK WIDURI, 2022)
Advice Planning is a recommendation regarding the explanation of land designation for development or building in an area so that it is in accordance with its land designation based on the urban spatial pattern plan as regulated in the Pangkalpinang City Regional Regulation Number 1 of 2012 concerning Regional Spatial Planning (RTRW). This Advice Planning is also an initial requirement that must exist in managing the development permit process in Pangkalpinang City. Submission of Advice Planning can be done on behalf of an individual or on behalf of a company. The submission process is also done manually by visiting the Pangkalpinang City Public Works and Spatial Planning Office to collect the requirements form. Then come back again to complete the file submitted by the applicant to the concerned agency and after completing the existing documents and requirements the applicant must wait a few days until the Advice Planning is issued. Therefore, to improve the quality of public services with the concept of e-Government and facilitate the community in the process of submitting Advice Planning, an Android-based Advice Planning service application is needed. So that public services will become easier and shorten the time. The results of the research are in the form of an android-based application which is expected to facilitate applicants in submitting Advice Planning to the Pangkalpinang City Government without being hindered by time and place.